Spontaneous Pneumomediastinum and Subcutaneous Emphysema in Dermatomyositis: A Case Series and Literature Review - Subki AH; Almani IM; Albeity A; Aljabri BK; Alsolaimani R; Halabi H (Journal of Inflammation Research, 2023)
Ahmed Hussein Subki,1 Ibraheem Mohammed Almani,2 Abdurahman Albeity,1 Bandari Khalid Aljabri,1 Roaa Alsolaimani,1,2 Hussein Halabi1 1Department of Medicine, King Faisal Specialist Hospital and Research Center, Jeddah, Saudi Arabia; 2Department of Medicine, King Abdulaziz University Hospital, Jeddah, Saudi ArabiaCorrespondence: Ahmed Hussein Subki; Hussein Halabi, Department of Internal Medicine, King Faisal Specialist Hospital & research center, POBox: 43129, Jeddah, 21561, Saudi Arabia, Tel +966566724288, Email subki.research@gmail.com; mfasel@gmail.comBackground: Spontaneous pneumomediastinum and subcutaneous emphysema are rare and serious complications of dermatomyositis (DM).Case Presentation: Our article presents two clinically heterogeneous cases of DM who developed pneumomediastinum and subcutaneous emphysema. The first was a 24-year-old lady with a recently diagnosed DM. She developed rapidly progressive pneumonia, interstitial lung disease (ILD), pneumomediastinum, subcutaneous emphysema, and acute respiratory distress syndrome (ARDS). She died despite treatment with steroids and immunosuppressants (methotrexate and mycophenolate mofetil (MMF)). The second was a 30-year-old man diagnosed with amyopathic DM. He developed pneumomediastinum prior to ILD, which worsened over time, and subcutaneous emphysema evolved. However, he recovered completely after corticosteroid, MMF, and rituximab.Conclusion: Spontaneous pneumomediastinum and subcutaneous emphysema may complicate DM. Corticosteroids, immunosuppressants, and respiratory support are the mainstay of management for these conditions. Though they were reported to carry a poor prognostic value, the course and outcome are highly variable among the cases.Keywords: dermatomyositis, pneumomediastinum, subcutaneous emphysema, pneumothorax, corticosteroids, immunosuppressants, rituximab